ANALYSIS OF INDUCTION MOTOR EFFICIENCY DECREASE DUE TO CAGE BALL BEARING DAMAGE - BILHAN GAMALIEL HARTANTO (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2024)
Induction motors, which convert electrical energy into mechanical energy using electromagnetic principles, are widely used in various applications from households to large industries. The performance of these motors is important for the smooth running of industrial production processes. Mechanical damage, such as bearing failure due to overload, can reduce their efficiency. This study aims to monitor and analyze the decrease in induction motor efficiency due to defects in the bearing cageball, using a literature review method. The results show a decrease in efficiency of around 2-3%, which is observed through the efficiency graph against the overall RMS.